1991
DOI: 10.2307/1963168
|View full text |Cite
|
Sign up to set email alerts
|

The Political Economy of Pork: Project Selection at The U.S. Army Corps of Engineers

Abstract: In previous studies of distributive politics scholars have investigated legislative influence without accounting for the policies' independent merits. As a result, they have failed to include a plausible explanation of the counterfactual (i.e., which projects would have been funded in the absence of congressional committee influence), which has led to invalid inferences regarding legislative influence. The model of distributive politics is reformulated to account for an assumed efficient and/or equitable proje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…Typical examples are allocation of military bases, highways, water projects and education facilities (Gilligan and Matsusaka 2001, Del Rossi 1995Del Rossi and Inman 1999;Hird 1991). Spending is negatively related to costbenefit ratios for US water projects, indicating that the suboptimality bias implied by the district demand model may be real (Hird 1991). Similar conclusions have been reached for centrally funded road expenditures in Norwegian counties (Elvik 1995).…”
Section: Existing Researchmentioning
confidence: 59%
See 1 more Smart Citation
“…Typical examples are allocation of military bases, highways, water projects and education facilities (Gilligan and Matsusaka 2001, Del Rossi 1995Del Rossi and Inman 1999;Hird 1991). Spending is negatively related to costbenefit ratios for US water projects, indicating that the suboptimality bias implied by the district demand model may be real (Hird 1991). Similar conclusions have been reached for centrally funded road expenditures in Norwegian counties (Elvik 1995).…”
Section: Existing Researchmentioning
confidence: 59%
“…The district demand model receives fairly strong empirical support where policies are geographically targetable in a strict sense. Typical examples are allocation of military bases, highways, water projects and education facilities (Gilligan and Matsusaka 2001, Del Rossi 1995Del Rossi and Inman 1999;Hird 1991). Spending is negatively related to costbenefit ratios for US water projects, indicating that the suboptimality bias implied by the district demand model may be real (Hird 1991).…”
Section: Existing Researchmentioning
confidence: 99%
“…The "ndings of many empirical studies suggest that politics may be responsible for large e$ciency losses (see Inman, 1988;Hird, 1991).…”
Section: New Deal Spendingmentioning
confidence: 99%
“…Through the examination of earmarks received by members in fiscal year 2008 Lazarus and Steigerwalt (2009) identify variables that influenced the earmark distribution; they find that organizational features, such as majority partisan control, affect individual member success. Their findings are supported by earlier, more policy-specific studies of funding requests in Congress that found institutional power (i.e., leadership in party and committee assignments) influences success in funding allocation (Balla et al 2002;Hird 1991;Roberts 1990). Other studies, however, suggest that district-level variables are better at predicting success than institutional power variables are (Anagnoson 1982;Arnold 1979;Rich 1989).…”
Section: Introductionmentioning
confidence: 60%